Visum Et Repertum Sebagai Alat Bukti dalam Menentukan Tuntutan Pidana terhadap Kasus Penganiayaan Berat - Ni Putu P Novi Widiantari; I Nyoman Gede Sugiartha; Ni Made Sukaryati Karma (Jurnal Interpretasi Hukum, 2022)
In Indonesian law, there is one piece of evidence called Visum et Repertum. The evidence is in the form of a statement from an expert in Judicial Medicine or Forensic Medicine obtained from the examination of the victim's body. The purpose of this study was to analyze the form of the Visum et Repertum equation as a valid evidence in the crime of serious maltreatment and to examine the strength of the proof of the post-mortem as evidence in determining the prosecution for cases of severe maltreatment. Visum et Repertum is one of the most important pieces of evidence in cases of severe abuse because it can assist judges in making decisions. This study uses a normative legal method which uses a statutory, conceptual, and deductive-inductive logical reasoning approach. The sources of the legal materials for this study are primary legal materials which contain the Criminal Code, the Criminal Procedure Code, the Law on the Principal Powers of Judges, the Law on the Indonesian Attorney General's Office, and the Law on the Indonesian National Police. Secondary legal materials consisting of: print and electronic literacy relevant to this . Data collection techniques used: library techniques and note-taking techniques, the data was collected then analyzed systematically through arguments formed from legal logic. This finds that Visum et Repertum is not explained directly in the Criminal Procedure Code, but the evidence from the examination relating to the body or life is considered valid and can be a consideration for judges in deciding a case with valid evidence.